Impact of global boycotts on Israeli goods: Evidence from Islamic and non-Islamic countries using an event study approach - Isa, Mohamad Yazid; Bahaman, Muhamad Abrar; Ahmad, Zaki; Islamkulov, Alimnazar; Ahmed, Mushtaq (Asian Economic and Financial Review, 2025)
The study examines the financial impact of consumer-led boycotts on the stock prices of companies affiliated with Israel in both Islamic and non-Islamic nations. Utilizing a rigorous event study methodology, this analysis considers a sample of four franchised companies from Muslim-majority countries (Malaysia and Indonesia) and three from non-Muslim countries (Japan and the USA), enabling a cross-cultural evaluation of market reactions to boycott events. The results indicate a modest adverse effect in Islamic countries, where minor declines in returns and price levels were observed during boycott periods. Non-Islamic countries, however, demonstrated a significantly positive abnormal return following boycott events, as evidenced by a consistent upward trend in Cumulative Average Abnormal Returns (CAAR). In Malaysia and Indonesia, the response was mixed, with both positive and negative impacts, suggesting inconclusive overall effects of boycotts on these economies. These findings imply that policymakers in Islamic nations may need to implement strategies to manage potential market volatility linked to boycott actions, while non-Islamic countries could develop policies to leverage observed market gains. The study further highlights the value of continued research into the effects of boycotts in Islamic markets, alongside the potential benefits of regional cooperation to promote more stable economic responses.